Macrozoobenthos Diversities in Ciwulan River, Tasikmalaya Regency, West Java - Muhammad Ridwan; Diana Hernawati; Popo Musthofa Kamil (Biotropika: Journal of Tropical Biology, 2020)
Ciwulan River is one of the longest rivers in Tasikmalaya Regency with a diversity of macrozoobenthos as one of the biota contained therein. The purpose of this study was to describe the diversity of macrozoobenthos in The Ciwulan River, Tasikmalaya Regency. This research is important because macrozoobenthos is a component in determining river bioindicators. The method used in this study is exploratory with a purposive sampling technique. Sampling of macrozoobenthos is done using a surber net and measurement of environmental indicators is done in situ at the observation station. Samples of macrozoobenthos were taken from three different stations including upstream Station I (Salawu), middle part II (Sukaraja), and downstream Station III (Cikalong). Data collection was carried out in November 2019-April 2020 in the Ciwulan River, Tasikmalaya Regency. Analysis of the observed data was then calculated relative abundance, cumulative abundance, diversity index, uniformity index, and dominance index. The results showed that the macrozoobenthos were found to have 24 species with 476 individuals/m2 belonging to the gastropod class as many as 21 species with 433 individual/m2, bivalve class two species with 37 individuals/m2 and crustacean class one species with six individuals/m2. Macrozoobenthos that are commonly found are Tarebia granifera Lamarck, 1822 totaling 222 individuals/m2. The highest relative abundance was found in Station I with the Tarebia granifera Lamarck species, 1822 which was 0.65%. and the lowest relative abundance was found in Station II with the species Lymnaea (Radix) rubiginosa Michelin, 1831 and Gyraulus convexiusculus Hutton, 1849 by 0.006%. Cumulative abundance values range from 54-350 individuals/m2. Diversity index values range from 1.02-1.67 with the category of moderate diversity. Uniformity index values ranged from 0.58 to 0.73 with a high category. The dominance index value ranges from 0.33 to 0.47 with the low category. Overall based on environmental parameters and ecological index measurements, the Ciwulan River is classified as not yet polluted and the conditions are suitable for macrozoobenthos life and have a moderate diversity of categories with relatively stable environmental conditions